The Use of Semantic Translation Method in Ḍau’u al-Misbāh fī Bayāni Ahkāmi al-Nikāh - Nauval Fitriah; Moch. Syarif Hidayatullah (ALSUNIYAT, 2020)
This study was aimed at investigating the use of semantic translation method in the translation of the Ḍau’u al-Misbāh fī Bayāni Ahkāmi al-Nikāh by K.H. Hasyim Asy'ari. A descriptive qualitative method was used in this study. After translating the data objects, the analysis process was carried out by describing the use of semantic translation method applied to translate the text. The results of this study revealed that semantic translation method used in translating Ḍau’u al-Misbāh fī Bayāni Ahkāmi al-Nikāh was an effective method to use in translating such classical texts, in which it eases the translator to produce translations that are acceptable in the target language (TL), easy to understand, and as closely as possible with the meaning of the sourch language (SL), and help the translator to preserve the writer's ideas.